Anti-Melanogenic Effects of Umbelliferone: In Vitro and Clinical Studies - Da Jung Kim; Min Sook Jung; Hee Un Jin; Mi Sun Kim; Chae Eun An (Molecules)
Melanin overexpression causes skin hyperpigmentation, which is associated with various skin disorders and cosmetic concerns. Umbelliferone, a natural coumarin found widely in plant species, has been noted for its antioxidant and anti-inflammatory effects but has received little attention for its impact on melanogenesis. Here, the effects of umbelliferone on melanogenesis were investigated in vitro and in clinical studies. The results showed that umbelliferone was non-cytotoxic to human skin and B16F10 melanoma cells. It also exhibited significant anti-melanogenic effects, reducing both melanin production and tyrosinase activity in a dose-dependent manner. This effect was achieved through a decrease in tyrosinase mRNA levels. Furthermore, umbelliferone in a formulation was stable under different temperature conditions, and after four weeks of topical application, it significantly decreased the melanin index and increased skin lightness (L*) values compared to those at the baseline. Overall, these findings demonstrate the potential of umbelliferone as a promising skin-lightening agent in the cosmetics industry.